Beispiel Nr: 03
$ \text{Gegeben:} \\ a1 \cdot x + b1\cdot y + c1\cdot z=d1\\ a2\cdot x + b2\cdot y + c2\cdot z=d2\\ a3\cdot x + b3\cdot y + c3\cdot z=d3\\ \\ \text{Gesucht:} \\\text{x,y,z} \\ \\ \textbf{Gegeben:} \\ 4 x -3 + 2 z=10\\ 5 x +6 y + -7 z=4\\ 10 x +2 y + -3 z=7\\ \\ \\ \textbf{Rechnung:} \\ 4 x + -3 y + 2 z=10\\ 5 x +6 y -7 z=4\\ 10 x +2 y -3 z=7\\ D_h=\left|\begin{array}{ccc} 4\ & -3 & 2\\ 5&6 & -7\\ 10& 2 & -3 \\ \end{array}\right| \begin{array}{cc} 4\ & -3 \\ 5&6 \\ 10& 2 \end{array} \\ D_h=4 \cdot 6 \cdot \left(-3\right)+\left(-3\right) \cdot \left(-7\right) \cdot 10 +2 \cdot 5 \cdot 2 - 2 \cdot 6 \cdot 10 -4 \cdot \left(-7\right) \cdot 2 -\left(-3\right) \cdot 5 \cdot \left(-3\right)=49 \\ D_x=\left|\begin{array}{ccc} 10\ & -3 & 2\\ 4&6 & -7\\ 7& 2 & -3 \\ \end{array}\right| \begin{array}{cc} 10\ & -3 \\ 4&6 \\ 7& 2 \end{array} \\ D_x=10 \cdot 6 \cdot \left(-3\right)+ \left(-3\right) \cdot \left(-7\right) \cdot 7 +2 \cdot 4 \cdot 2 - 2 \cdot 6 \cdot 7 - 10 \cdot \left(-7\right) \cdot 2 -\left(-3\right) \cdot 4 \cdot \left(-3\right)=3\\ D_y=\left|\begin{array}{ccc} 4\ & 10 & 2\\ 5&4 & -7\\ 10& 7 & -3 \\ \end{array}\right| \begin{array}{cc} 4\ & 10 \\ 5&4 \\ 10& 7 \end{array} \\ D_y=4 \cdot 4 \cdot \left(-3\right)+10 \cdot \left(-7\right) \cdot 10 +2 \cdot 5 \cdot 7 - 2 \cdot 4 \cdot 10 -4 \cdot \left(-7\right) \cdot 7 -10 \cdot 5 \cdot \left(-3\right)=-412 \\ D_z=\left|\begin{array}{ccc} 4\ & -3 & 10\\ 5&6 & 4\\ 10& 2 & 7 \\ \end{array}\right| \begin{array}{cc} 4\ & -3 \\ 5&6 \\ 10& 2 \end{array} \\ D_z=4 \cdot 6 \cdot 7+\left(-3\right) \cdot 4 \cdot 10 +10 \cdot 5 \cdot 2 - 10 \cdot 6 \cdot 10 -4 \cdot 4 \cdot 2 -\left(-3\right) \cdot 5 \cdot 7=-379\\ x=\frac{3}{49} \\ x=\frac{3}{49} \\ y=\frac{-412}{49} \\ y=-8\frac{20}{49} \\ z=\frac{-379}{49} \\ z=-7\frac{36}{49}\\ L=\{\frac{3}{49}/-8\frac{20}{49}/-7\frac{36}{49}\} $